A Comparative Analysis of the Use of Microfinance and Formal and Informal Credit by Farmers in Less Developed Areas of Rural China. (March 2015) - Jia, Xiangping; Luan, Hao; Huang, Jikun; Li, Zuowen
<x xml:space="preserve">Abstract</x> Based on household survey data, this article shows that farmers' demand for credit in poor areas of rural China has increased significantly in recent years, and credits from various sources are used differently in production and consumption. For example, microfinance is used primarily in livestock and non‐agricultural investments, formal credit is often used in crop production, and informal credit is largely used to meet farmers' consumption requirements. Developing a complementary system with various financial channels in rural China, particularly for non‐governmental microfinance, is crucial for meeting farmers' rising demand for credit in both production and consumption.